Dasar Keagamaan Gerakan Islam Muhammadiyah Indonesia - Mira Yanti Lubis; Ahmad Lahmi; Dasrizal Dahlan (Jurnal Teologi Islam, 2026)
The Muhammadiyah Islamic movement, founded by KH Ahmad Dahlan on 18 November 1912, emerged as a response to the socio-religious degradation under colonial rule, grounding its religious orientation in the purification of Islamic creed based on the Qur’an and Sunnah from elements of shirk, bid‘ah, and khurafat. Through the concept of Islam Berkemajuan (Progressive Islam), Muhammadiyah integrates pure monotheism, progressive renewal (tajdid), the principles of amar ma’ruf nahi munkar, and the vision of rahmatan lil ‘alamin as an embodiment of the ummatan wasathan (the justly balanced community). This study employs a library research method by analyzing several historical works on Muhammadiyah, foundational doctrinal texts (Matan Keyakinan), and academic articles from the Majelis Tarjih scientific archives. Muhammadiyah is an Islamic reform movement in Indonesia that seeks to eliminate bid‘ah, superstition, and khurafat from societal culture. Rooted in the Qur’an and Hadith, Muhammadiyah is committed to developing sound, pure, and enlightened religious thought.